1995
DOI: 10.1152/jn.1995.74.4.1675
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive consequences of tendon vibration during movement

Abstract: 1. Previous studies have used tendon vibration to investigate kinesthetic illusions in the isometric limb and end point control in the moving limb. These previous studies have shown that vibration distorts the perceptions of static joint angle and movement and causes systematic errors in the end point of movement. In this paper we describe the effects of tendon vibration during movement while human subjects performed a proprioceptively coordinated motor task. In an earlier study we showed that the CNS coordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
111
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(117 citation statements)
references
References 0 publications
4
111
0
2
Order By: Relevance
“…This stimulation, which can cause kinesthetic illusions of muscle lengthening, has also been demonstrated to have longer term effects after removal of the vibration (Cordo et al, 1995, Shinohara, 2005, Wierzbicka et al, 1998. These effects include increases in the discharge threshold of the Ia afferents and inhibition of Ia terminals (Hayward et al, 1986, Hultborn et al, 1987, Shinohara, 2005.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This stimulation, which can cause kinesthetic illusions of muscle lengthening, has also been demonstrated to have longer term effects after removal of the vibration (Cordo et al, 1995, Shinohara, 2005, Wierzbicka et al, 1998. These effects include increases in the discharge threshold of the Ia afferents and inhibition of Ia terminals (Hayward et al, 1986, Hultborn et al, 1987, Shinohara, 2005.…”
Section: Discussionmentioning
confidence: 97%
“…Both of these effects have been attributed to muscle spindle organ sensitivity to vibration (Cordo et al, 1995, Feldman and Latash, 1982, Roll and Vedel, 1982, Shinohara, 2005, Wierzbicka et al, 1998.…”
Section: Introductionmentioning
confidence: 99%
“…We think this choice is justifiable for two reasons. First, results in microneurography studies have demonstrated a major role of muscle spindles in proprioception (Cordo et al 1995;Goodwin et al 1972a;Roll and Vedel 1982) and muscle spindles are the primary sensory resource of information for maintaining balance during upright stance . Second, anesthetizing joint receptors only results in an increased positioning error in passive repositioning (Konradsen et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Muscle spindles play a major role in proprioception (Cordo et al 1995;Goodwin et al 1972a;Roll and Vedel 1982). In studies on the role of proprioception in standing, vibration is used to analyze the relative contribution of a peripheral proprioceptive signal to the total motor output.…”
Section: Introductionmentioning
confidence: 99%
“…Vibration to the muscles alters afferent discharge of muscle spindles [31], which in turn can affect the body perception [32]. The alterations in afferent discharge results in excitatory or inhibitory input on a-motoneurons, depending on the duration of the applied vibration [33] and the frequency of the vibration intensity.…”
Section: Joint Position Sensementioning
confidence: 99%